SOLID DISPERSIONS: AN OVERVIEW ON SOLUBILITY ENHANCEMENT OF POORLY WATER SOLUBLE DRUGS - PARVE BALASAHEB; TELI BALAJI; BIRAJDAR AVINASH (International Journal of Pharma and Bio Sciences, 2014)
Improving oral bioavailability of solid dosage forms is a challenge for the formulation scientists due to their solubility problems. The dissolution rate could be the rate-limiting step in the absorption of poorly water soluble drugs Solid dispersion techniques have attracted considerable interest of improving the dissolution rate of highly lipophilic drugs thereby improving their bioavailability by reducing drug particle size, improving wettability and forming amorphous particles. This strategy has proven to improve the bioavailability by dispersing the lipophilic drug as very fine particles within hydrophilic matrix that results in increased solubility with increased surface area available for dissolution. This article reviews the need for the solubility enhancement of poorly water soluble drugs, historical background, advantages, disadvantages, various categories of solid dispersions, manufacturing methods, factors influencing the drug release, characterization of solid dispersions.